Exploring Hardware Heterogeneity to Improve Pervasive Context Inferences - Chenguang Shen; Srivastava, Mani (Computer (Long Beach, Calif.), 2017)
Context-aware inference apps have become pervasive as a result of the Internet of Things (IoT). However, most of these apps run continuously on a single device, resulting in limited sensor coverage and high energy consumption. Recent advances in IoT devices, specifically hardware heterogeneity, can be leveraged to improve the accuracy and energy efficiency of context inferences.